Building a better Chicago : race and community resistance to urban redevelopment - Gonzales, Teresa Irene (Latina/o sociology series., 2021)
"This book offers insight into how redevelopment policy is implemented on the ground, articulates the political and social benefits of collective skepticism for communities of color, and critiques the partial perspectives dominant in social capital and community development studies"--